Mesoporous silicon-based material prepared based on coal gasification slag and phase change material

The preparation of mesoporous silicon-based material through coal gasification slag coated with paraffin to form mesoporous silicon-based phase change composite materials, which solves the problem of liquid flow during paraffin phase change, improves the safety and recycling rate of the heat storage system, and promotes the high value-added utilization of coal gasification slag.

CN119873837AActive Publication Date: 2025-04-25HUAXIN CEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510020751.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Existing phase-change heat storage materials such as paraffin will melt into liquid during the phase-change process, causing the safety of the heat storage system to be threatened and the efficiency of its recycling. At the same time, the high added value of coal gasification slag is insufficient, resulting in energy waste and environmental pollution.

Method used

Mesoporous silicon-based materials are prepared by using coal gasification slag and used to coat paraffin wax to form mesoporous silicon-based phase change composite materials. The material has a high specific surface area, large pore capacity and high spatial structural strength, which can limit the flow of paraffin and improve the safety and recycling rate of the heat storage system.

Benefits of technology

The solid-solid phase transformation of paraffin phase change materials is realized, the safety and recycling rate of the heat storage system are enhanced, and the industrial solid waste coal gasification slag is utilized, which improves resource utilization and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873837A_ABST
    Figure CN119873837A_ABST
Patent Text Reader

Abstract

The invention discloses a meso-porous silicon-based material prepared on the basis of coal gasification slag and a phase change material. The meso-porous silicon-based material prepared on the basis of the coal gasification slag has a spatial three-dimensional network structure, the pore diameter is 5-30 nm, the specific surface area is 550-900 m < 2 > / g, and the pore volume is 0.45-0.80 cm < 3 > / g. The industrial solid waste coal gasification slag is used as a raw material, the mesoporous silicon-based material capable of being applied in the industry is obtained through modification treatment, the mesoporous silicon-based material has the large specific surface area and the high structural strength and can be compounded with paraffin to obtain the mesoporous silicon-based phase change composite material, and the prepared mesoporous silicon-based phase change composite material is high in structural strength, light in weight, high in heat conductivity and good in thermal conductivity. The prepared phase-change material has excellent strength and thermal conductivity when applied to a cement-based material, not only can well solve the problem that the phase-change material paraffin of a heat storage system is easy to flow out, but also can improve the problem that the heat storage cycle efficiency of the phase-change material is low, so that the phase-change material has a large-scale application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of materials that undergo physical state changes when used, and specifically relates to a mesoporous silicon-based material and a phase change material prepared based on coal gasification slag. Background Art

[0002] Thermal energy is one of the most common energy sources in people's production and life, but the use of thermal energy is time-sensitive, which leads to a large amount of thermal energy not being effectively utilized and being directly discharged, causing energy waste.

[0003] Thermal energy storage technology not only solves the problem of timeliness of thermal energy supply, but also reduces the cost of energy system. Phase change heat storage, one of the thermal energy storage technologies, is based on the principle of heat storage and release by using the property of phase change materials that absorb or release heat and keep the temperature unchanged when phase change occurs. The selection principle of phase change materials is that the material itself has a high latent heat value, no supercooling or no obvious supercooling phenomenon, non-toxic, low cost, abundant sources, and stable properties. Paraffin-based phase change materials have the above properties, and their latent heat value is 150-230 J / g. They are a mixture of various alkanes. The phase change temperature and latent heat are related to the length and structure of the carbon chain. Therefore, paraffin with the required phase change temperature can be obtained by changing the length and structure of the paraffin carbon chain, which greatly increases the scope of application of this type of material. Although paraffin has the above advantages, since paraffin is a solid-liquid phase change material, it will melt into liquid when phase change occurs, which threatens the safety of the heat storage system and reduces its recycling efficiency. Therefore, it needs to be modified in order to obtain a solid-solid phase change material.

[0004] my country's total coal consumption is huge every year. During the processing and conversion process, a large amount of coal gasification slag solid waste is generated, but most of them are landfilled as the main treatment method. The harmful substances in them will cause serious pollution to the atmosphere, soil and groundwater. How to use coal gasification slag with high added value is imminent.

[0005] The present invention uses solid waste material coal gasification slag to prepare mesoporous silicon-based materials, and then uses the mesoporous silicon-based materials to encapsulate paraffin to limit the flow of liquid after the paraffin is melted, which not only enhances the safety of the heat storage system, but also improves its recycling rate. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a mesoporous silicon-based material and a phase change material prepared based on coal gasification slag in view of the deficiencies in the prior art. The mesoporous silicon-based material has a high specific surface area and a large pore volume, and its spatial network structure is also high in strength. After being coated with paraffin, it is made into a phase change material and applied in cement-based materials - insulation mortar or insulation board, which has the advantages of low density, high strength and good thermal conductivity.

[0007] The present invention provides a mesoporous silicon-based material prepared based on coal gasification slag, which has a spatial three-dimensional network structure, a pore size of 5-30nm, and a specific surface area of ​​550-900m 2 / g, pore volume is 0.45-0.80cm 3 / g.

[0008] The present invention also provides a preparation method of the above-mentioned mesoporous silicon-based material based on coal gasification slag: the coal gasification slag is dried and then ground, activated at high temperature and then acid-leached to remove impurities to obtain coal gasification acid leaching slag, the obtained coal gasification acid leaching slag is mixed with NaOH and Na2SiO3, reacted at high temperature and water-leached to obtain an alkali-melted product, the obtained alkali-melted product is modified with a cationic surfactant to obtain a coal gasification slag enhanced precursor, the obtained coal gasification slag enhanced precursor is subjected to a condensation reaction with silane to obtain a coal gasification slag wet gel, the obtained coal gasification slag wet gel is then subjected to surface enhancement treatment, aging, solvent replacement and surface modification, and finally cleaned and dried to obtain a mesoporous silicon-based material.

[0009] According to the above scheme, the SiO2 content in the coal gasification slag is not less than 40%, and the ignition loss is not higher than 15%.

[0010] According to the above scheme, the cationic surfactant is hexadecyltrimethylammonium bromide.

[0011] According to the above scheme, the silane is methyltrimethoxysilane and methyltriethoxysilane.

[0012] The preparation method of the mesoporous silicon-based material prepared from coal gasification slag comprises the following specific steps:

[0013] Step 1: Dry the coal gasification slag to constant weight and grind it into powder using a planetary ball mill to make its specific surface area not less than 350m 2 / g, then subjecting the ground coal gasification slag to high temperature activation and grinding to obtain activated coal gasification slag, mixing the obtained activated coal gasification slag with a mixed acid of hydrochloric acid and acetic acid to acid leaching reaction, separating the solid and the liquid after the reaction, washing the obtained filter residue, and drying to obtain coal gasification acid leaching residue;

[0014] Step 2: Mix the coal gasification acid leaching residue obtained in step 1 with NaOH and Na2SiO3, heat to react, take out after the reaction is completed, quench in cold water, separate the solid and liquid to obtain a precipitate, wash and dry the precipitate to obtain an alkali-melted product;

[0015] Step 3: dissolving the alkali-melted product obtained in step 2 with water to obtain an alkali-melted solution, adding a cationic surfactant and an aqueous ammonia solution (0.1-0.5 mol / L), stirring for 0.5-3 h, and then adding an acetic acid solution (0.5-1 mol / L) dropwise to the obtained mixed solution to adjust the pH value of the system to 8-12, and continuing to stir for 8-24 h to obtain a coal gasification slag enhanced precursor;

[0016] Step 4: Mix the coal gasification slag enhancement precursor obtained in step 3 with the silane mixed solution, add a catalyst, and finally add an ammonia solution (0.1-0.5 mol / L) to adjust the pH value of the system to 10-12, and perform a gelation reaction to obtain a coal gasification slag wet gel;

[0017] Step 5. Add sodium dodecylbenzene sulfonate to the coal gasification slag wet gel obtained in step 4 to enhance the wet gel to obtain an enhanced wet gel. Place the enhanced wet gel in anhydrous ethanol for aging treatment to obtain an aged gel after the aging treatment. Then, replace the aqueous phase solution in the pores of the aged gel with anhydrous ethanol for multiple times. Place the replaced gel in a silane solution for surface modification. After the modification, wash it with n-hexane and dry it at normal pressure to obtain a mesoporous silicon-based material.

[0018] According to the above scheme, the high temperature activation process conditions in step 1 are: heating at 600-950°C for 0.5-2h. The residual carbon and other salt components in the coal gasification slag are decomposed by high temperature activation, and the remaining substance is high temperature activated silicon oxide.

[0019] According to the above scheme, the concentration of hydrochloric acid in the mixed acid of hydrochloric acid and acetic acid in step 1 is 0.1-0.5 mol / L, the concentration of acetic acid is 0.5-1 mol / L, the solid-liquid ratio of the coal gasification slag to the mixed acid of hydrochloric acid and acetic acid is 0.14-0.30 g / L; the acid leaching reaction conditions are: reacting at 80-120°C for 1-4 hours. The purpose of acid leaching treatment is to remove impurities, dissolve oxides such as iron / aluminum / magnesium in the coal gasification slag, and leave silicon dioxide residue; secondly, hydrochloric acid and acetic acid have a certain activation effect, hydrochloric acid is conducive to activating calcium aluminum silicate and hematite in the coal gasification slag, and acetic acid can react with the Ca phase in the coal gasification slag to generate acetic acid aluminum hydroxide hydrate ((CH3COO)2Al(OH)) and hydrocarburite (CaAl2(CO3)2(OH)4·3H2O).

[0020] According to the above scheme, the mass ratio of coal gasification acid leaching residue to NaOH and Na2SiO3 in step 2 is 1:1-2:0.5-1.5. Preferably, it is 1:1-1.5:0.5-1.0. The main component of coal gasification acid leaching residue is SiO2. NaOH can react with SiO2 to form active sodium silicate. The Na2SiO3 added to the system can provide a certain alkaline environment and soluble Si during the reaction. Na2SiO3 hydrolyzes to form silicate colloid Si(OH)4 and produces a large amount of OH - ions, silicate colloid Si(OH)4 has adsorption properties with [OSi(OH)3] and [OSi(OH)3] produced by coal gasification slag in an alkaline environment 2-The network-like gels such as hydrated monomers and dimers adsorb each other to form a dense spatial network structure that is intertwined and connected, optimizing the pore structure and improving the strength.

[0021] According to the above scheme, the heating reaction conditions in step 2 are: reaction at 550-800°C for 1-4h.

[0022] According to the above scheme, the concentration of the alkaline solution in step three is 20-60wt%.

[0023] According to the above scheme, the mass ratio of the alkaline molten product in step 3 to the cationic surfactant and the ammonia water in the ammonia solution is 1:0.1-0.8:2-8, preferably 1:0.1-0.4:4-7.

[0024] According to the above scheme, the silane mixed solution is obtained by mixing methyltrimethoxysilane, methyltriethoxysilane, anhydrous ethanol and isopropanol in a mass ratio of 1:2:50:30.

[0025] According to the above scheme, the catalyst is obtained by mixing ammonium fluoride and dimethylformamide in a mass ratio of 1:5.

[0026] According to the above scheme, the mass ratio of the coal gasification slag enhancement precursor, the silane mixed solution and the catalyst in step 4 is 1-5: 5-10: 0.1-0.5, preferably 1-3: 5-8: 0.1-0.3.

[0027] According to the above scheme, the gelation reaction conditions in step 4 are: reaction at 40-75°C for 4-12 hours.

[0028] According to the above scheme, the mass ratio of the coal gasification slag wet gel to sodium dodecylbenzene sulfonate in step 5 is 1:0.1-0.5, preferably 1:0.1-0.3.

[0029] According to the above scheme, the enhancement treatment time in step 5 is 8-16 hours, preferably 8-12 hours. The enhancement treatment of the present invention can regulate the chemical composition of the gel and improve the uniformity and strength of the skeleton structure of the gel precursor.

[0030] According to the above scheme, the aging treatment temperature in step 5 is 45-55°C and the time is 8-20 hours, preferably 12-20 hours.

[0031] According to the above scheme, the silane solution in step 5 is obtained by mixing trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol in a volume ratio of 1-5:1-8:6-12:2-6, preferably 1-3:1-5:6-10:2-5.

[0032] According to the above scheme, the mass ratio of the replaced gel to the silane solution in step 5 is 1:2-4.

[0033] According to the above scheme, the surface modification time in step 5 is 12-48 hours, preferably 12-36 hours.

[0034] The present invention also includes a mesoporous silicon-based phase change composite material prepared according to the above mesoporous silicon-based material.

[0035] The preparation method of the above-mentioned mesoporous silicon-based phase change composite material is as follows: the mesoporous silicon-based material and paraffin are mixed in a mass ratio of 1:0.2-0.8, and the paraffin is dispersed in the internal pores of the mesoporous silicon-based material by ultrasonic vibration at 70-120°C (preferably 85-110°C) to obtain a mesoporous silicon-based phase change composite material.

[0036] Preferably, the mass ratio of the mesoporous silica-based material to paraffin is 1:0.3-0.6.

[0037] According to the above scheme, the ultrasonic oscillation time is 0.2-2h (preferably 0.5-2h).

[0038] The present invention also includes a thermal insulation board prepared according to the above mesoporous silicon-based phase change composite material.

[0039] The specific preparation method of the above-mentioned insulation board is as follows: first, 40 parts of PO 42.5 cement, 8 parts of pulp fiber, 30 parts of 0.6-2.26mm ceramic sand, 20 parts of water, and 2 parts of the above-prepared mesoporous silicon-based phase change composite material are mixed evenly with a mortar mixer, and then poured into a 150mm×150mm mold, and then a press is used to pressurize to 5MPa with a force of 0.1MPa / s, and the pressure is maintained for 3 minutes to obtain a 150mm×150mm×5mm insulation board blank, and finally the insulation board blank is standard cured for 7-14d to obtain an insulation board.

[0040] Although coal gasification slag contains certain aluminosilicate substances, it is difficult to effectively utilize the silicon element therein to prepare mesoporous silicon with certain structural strength and meeting the requirements of practical applications due to the high impurity content. The present invention first removes impurities by calcination and acid leaching, then reacts with alkali, calcines, and quenches with cold water to obtain an alkali-melted product, and then uses hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate as surface enhancers to prepare wet gel. Through the two enhancements, the sol particles and small clusters are attached and grown in the solution to form clusters to expand the gel network, and the condensation reaction of the gel continues to cross-link. Through cross-linking, the gel can be In order to continue to strengthen or reinforce the network structure, a wet gel with stable performance, high porosity and low density is finally obtained. The surface of the gel is modified by a silane solution obtained by mixing trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol, which can alkylate the silicon light groups on the surface of the gel. The surface of the modified gel pores is grafted with hydrophobic groups to reduce the capillary pressure, avoid excessive shrinkage and structural collapse of the gel during drying, enhance the strength of the mesoporous silica-based material, and help it maintain a spatial network structure. The mesoporous silica-based material finally prepared has a large specific surface area and pore volume, as well as high spatial structural strength. The phase change material prepared by coating paraffin with the mesoporous silica-based material can be applied to cement-based materials, such as preparing insulation boards, etc., and has excellent strength and thermal conductivity, and is also lightweight, low-density and highly safe.

[0041] The beneficial effects of the present invention are as follows: 1. The present invention uses industrial solid waste coal gasification slag as raw material, and obtains a mesoporous silicon-based material that can be applied in industry through modification treatment. The mesoporous silicon-based material has a large specific surface area and high structural strength, and can be compounded with paraffin to obtain a mesoporous silicon-based phase change composite material. The prepared mesoporous silicon-based phase change composite material has high structural strength, light weight, and high thermal conductivity. It has excellent strength and thermal conductivity when applied to cement-based materials. It can not only solve the problem of easy outflow of paraffin in the phase change material of the heat storage system, but also improve the problem of low heat storage cycle efficiency of the phase change material, and thus has a large-scale application prospect;

[0042] 2. The preparation method provided by the present invention has relatively simple steps, low requirements on process conditions, good repeatability, less pollution to the environment, can improve the utilization rate and added value of solid waste materials, and has high environmental and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a SEM image of the mesoporous silicon-based material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present application will be clearly and completely described below.

[0045] There is no particular limitation on the specific dispersing and stirring methods in the present application, as long as the purpose of dispersing and stirring is achieved.

[0046] The raw materials used in the embodiments and comparative examples are described as follows: the SiO2 content in the coal gasification slag used is 43.9%, and the ignition loss is 12.2%. The hexadecyltrimethylammonium bromide, methyltrimethoxysilane, methyltriethoxysilane, anhydrous ethanol and isopropanol used are purchased from Aladdin Reagent Company; ammonium fluoride, dimethylformamide, sodium dodecylbenzenesulfonate, trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine, polyethylene glycol (PEG-400) and anhydrous ethanol are purchased from Sinopharm Group Reagent Company; hydrochloric acid, acetic acid, ammonia water, sodium silicate, sodium hydroxide and other component raw materials are all commercially available raw materials unless otherwise specified.

[0047] Example 1

[0048] A method for preparing a mesoporous silicon-based material based on coal gasification slag comprises the following steps:

[0049] Step 1: Dry the coal gasification slag in an oven at 105°C to constant weight, and use a planetary ball mill to ball mill the dried coal gasification slag for 0.5h. The specific surface area of ​​the ball milled product is 350m 2 / g, and then the ground coal gasification slag is placed in a muffle furnace and calcined at 950℃ for 0.5h, and then ground with a glass mortar to make it all pass through a 75-micron square hole sieve to obtain activated coal gasification slag, weigh 100g of the activated coal gasification slag, and place it in a 500mL three-necked flask, hydrochloric acid (0.5mol / L) and acetic acid (1mol / L) are mixed in a volume ratio of 1:1 to form a mixed acid, and then the mixed acid is added to the three-necked flask according to a solid-liquid ratio of 0.2g / L, and stirred for 3h under 95℃ oil bath heating conditions, and the stirring rate is 500rpm. After the reaction is completed, the solid-liquid separation is carried out by suction filtration to obtain an acid leaching solution and an acid leaching residue, and the acid leaching residue is rinsed with a large amount of deionized water until the washing filtrate is titrated with an AgNO3 solution without white precipitation or turbidity, and the washed acid leaching residue is placed in an oven at 105℃ and dried for 24h to obtain coal gasification acid leaching residue;

[0050] Step 2: Mix the coal gasification acid leaching residue obtained in step 1 with NaOH and Na2SiO3 in a mass ratio of 1:1.2:1.0, heat in a muffle furnace at 550°C for 1 hour, take out, quench in cold water, separate the solid from the liquid by suction filtration, rinse the obtained precipitate with distilled water for 10 times, and then place in a vacuum drying oven at room temperature and vacuum dry for 48 hours to obtain an alkali-melted product;

[0051] Step 3: dissolving the alkali-melted product obtained in step 2 in water to obtain an alkali-melted solution with a concentration of 40 wt%, and mixing it with hexadecyltrimethylammonium bromide and ammonia water in an ammonia solution (0.2 mol / L) at a mass ratio of 1:0.2:5, stirring for 1 hour, adding acetic acid solution (0.6 mol / L) dropwise to the system, adjusting the pH value of the system to 10, and continuing to stir for 12 hours to obtain a coal gasification slag enhanced precursor;

[0052] Step 4: Mix the coal gasification slag enhancement precursor obtained in step 3 with a silane mixed solution (mixed by methyltrimethoxysilane, methyltriethoxysilane, anhydrous ethanol, and isopropanol in a mass ratio of 1:2:50:30), then add catalysts ammonium fluoride and dimethylformamide (the mass ratio of ammonium fluoride to dimethylformamide is 1:5), and finally add an ammonia solution (0.2 mol / L) to adjust the pH value of the system to 11. The mass ratio of the above precursor: silane mixed solution: catalyst is 1.5:6:0.1, the temperature is adjusted to 60°C, and the reaction is carried out for 8 hours to obtain a coal gasification slag wet gel;

[0053] Step 5. Add sodium dodecylbenzene sulfonate to the gasification slag wet gel obtained in step 4 to enhance the wet gel. The mass ratio of the gasification slag wet gel to sodium dodecylbenzene sulfonate is 1:0.15. The reaction time is 8 hours to obtain an enhanced wet gel. The enhanced wet gel is immersed in anhydrous ethanol for aging treatment. The aging temperature is 50°C and the aging time is 16 hours. After the aging treatment, an aged gel is obtained. The aqueous phase solution in the pores of the aged gel is replaced with anhydrous ethanol multiple times. The replaced gel is then placed in a silane solution for solvent replacement and surface modification to alkylate the silanol group on the gel surface. The silane solution is obtained by mixing trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol in a volume ratio of 1:2:6:3. The mass ratio of the replaced gel to the silane solution is 1:3. After modification for 12 hours, it is washed with n-hexane and finally dried at normal pressure to obtain a mesoporous silicon-based material.

[0054] The mesoporous silicon-based material prepared in this embodiment is used to prepare a mesoporous silicon-based phase change composite material. The specific preparation method is as follows: the above-mentioned mesoporous silicon-based material and paraffin are mixed in a mass ratio of 1:0.3, and the paraffin is dispersed in the internal pores of the mesoporous silicon-based material by ultrasonic oscillation at 90°C. The ultrasonic oscillation time is 1 hour to obtain a mesoporous silicon-based phase change composite material.

[0055] Example 2

[0056] A method for preparing a mesoporous silicon-based material based on coal gasification slag comprises the following steps:

[0057] Step 1: Dry the coal gasification slag in an oven at 105°C to constant weight, and use a planetary ball mill to ball mill the dried coal gasification slag for 0.5h. The specific surface area of ​​the ball milled product is not less than 350m 2 / g, and then the ground coal gasification slag is placed in a muffle furnace and calcined at 950℃ for 0.5h, and then ground with a glass mortar to make it all pass through a 75-micron square hole sieve to obtain activated coal gasification slag, weigh 100g of the activated coal gasification slag, and place it in a 500mL three-necked flask, hydrochloric acid (0.5mol / L) and acetic acid (1mol / L) are mixed in a volume ratio of 1:1 to form a mixed acid, and then the mixed acid is added to the three-necked flask according to a solid-liquid ratio of 0.2g / L, and stirred for 3h under 95℃ oil bath heating conditions, and the stirring rate is 500rpm. After the reaction is completed, the solid-liquid separation is carried out by suction filtration to obtain an acid leaching solution and an acid leaching residue, and the acid leaching residue is rinsed with a large amount of deionized water until the washing filtrate is titrated with an AgNO3 solution without white precipitation or turbidity, and the washed acid leaching residue is placed in an oven at 105℃ and dried for 24h to obtain coal gasification acid leaching residue;

[0058] Step 2: Mix the coal gasification acid leaching residue obtained in step 1 with NaOH and Na2SiO3 in a mass ratio of 1:1.2:1.0, heat in a muffle furnace at 550°C for 1 hour, take out, quench in cold water, separate the solid from the liquid by suction filtration, rinse the obtained precipitate with distilled water for 10 times, and then place in a vacuum drying oven at room temperature and vacuum dry for 48 hours to obtain an alkali-melted product;

[0059] Step 3: dissolving the alkali-melted product obtained in step 2 in water to obtain an alkali-melted solution with a concentration of 40 wt%, and mixing it with hexadecyltrimethylammonium bromide and ammonia water in an ammonia solution (0.2 mol / L) in a mass ratio of 1:0.3:6, stirring for 1 hour, adding acetic acid solution (0.6 mol / L) dropwise to the system, adjusting the pH value of the system to 10, and continuing to stir for 12 hours to obtain a coal gasification slag enhanced precursor;

[0060] Step 4: Mix the coal gasification slag enhancement precursor obtained in step 3 with a silane mixed solution (mixed by methyltrimethoxysilane, methyltriethoxysilane, anhydrous ethanol, and isopropanol in a mass ratio of 1:2:50:30), then add catalysts ammonium fluoride and dimethylformamide (the mass ratio of ammonium fluoride to dimethylformamide is 1:5), and finally add an ammonia solution (0.2 mol / L) to adjust the pH value of the system to 11. The mass ratio of the above precursor: silane mixed solution: catalyst is 2:7:0.2, the temperature is adjusted to 60°C, and the reaction is carried out for 10 hours to obtain a coal gasification slag wet gel;

[0061] Step 5: Add sodium dodecylbenzene sulfonate to the coal gasification slag wet gel obtained in step 4 to enhance the wet gel. The mass ratio of the coal gasification slag wet gel to sodium dodecylbenzene sulfonate is 1:0.2. The reaction time is 10 hours to obtain an enhanced wet gel. The enhanced wet gel is immersed in anhydrous ethanol for aging treatment. The aging temperature is 50°C and the aging time is 20 hours. After the aging treatment, an aged gel is obtained. The aqueous phase solution in the pores of the aged gel is replaced with anhydrous ethanol multiple times. The replaced gel is then placed in a silane solution for solvent replacement and surface modification to alkylate the silanol group on the gel surface. The silane solution is obtained by mixing trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol in a volume ratio of 2:3:7:4. The mass ratio of the replaced gel to the silane solution is 1:3. After modification for 16 hours, it is washed with n-hexane and finally dried at normal pressure to obtain a mesoporous silicon-based material.

[0062] The mesoporous silicon-based material prepared in this embodiment is used to prepare a mesoporous silicon-based phase change composite material. The specific preparation method is as follows: the above-mentioned mesoporous silicon-based material and paraffin are mixed in a mass ratio of 1:0.3, and the paraffin is dispersed in the internal pores of the mesoporous silicon-based material by ultrasonic oscillation at 90°C. The ultrasonic oscillation time is 1 hour to obtain a mesoporous silicon-based phase change composite material.

[0063] Example 3

[0064] A method for preparing a mesoporous silicon-based material based on coal gasification slag comprises the following steps:

[0065] Step 1: Dry the coal gasification slag in an oven at 105°C to constant weight, and use a planetary ball mill to ball mill the dried coal gasification slag for 0.5h. The specific surface area of ​​the ball milled product is not less than 350m 2 / g, and then the ground coal gasification slag is placed in a muffle furnace and calcined at 950℃ for 0.5h, and then ground with a glass mortar to make it all pass through a 75-micron square hole sieve to obtain activated coal gasification slag, weigh 100g of the activated coal gasification slag, and place it in a 500mL three-necked flask, hydrochloric acid (0.5mol / L) and acetic acid (1mol / L) are mixed in a volume ratio of 1:1 to form a mixed acid, and then the mixed acid is added to the three-necked flask according to a solid-liquid ratio of 0.2g / L, and stirred for 3h under 95℃ oil bath heating conditions, and the stirring rate is 500rpm. After the reaction is completed, the solid-liquid separation is carried out by suction filtration to obtain an acid leaching solution and an acid leaching residue, and the acid leaching residue is rinsed with a large amount of deionized water until the washing filtrate is titrated with an AgNO3 solution without white precipitation or turbidity, and the washed acid leaching residue is placed in an oven at 105℃ and dried for 24h to obtain coal gasification acid leaching residue;

[0066] Step 2: Mix the coal gasification acid leaching residue obtained in step 1 with NaOH and Na2SiO3 in a mass ratio of 1:1.2:1.0, heat in a muffle furnace at 550°C for 1 hour, take out, quench in cold water, separate the solid from the liquid by suction filtration, rinse the obtained precipitate with distilled water for 10 times, and then place in a vacuum drying oven at room temperature and vacuum dry for 48 hours to obtain an alkali-melted product;

[0067] Step 3: dissolving the alkali-melted product obtained in step 2 with water to obtain an alkali-melted solution with a concentration of 40 wt%, and mixing it with hexadecyltrimethylammonium bromide and ammonia water in an ammonia solution (0.2 mol / L) at a mass ratio of 1:0.4:7, stirring for 1 hour, adding acetic acid solution (0.6 mol / L) dropwise to the system, adjusting the pH value of the system to 10, and continuing to stir for 12 hours to obtain a coal gasification slag enhanced precursor;

[0068] Step 4: Mix the coal gasification slag enhancement precursor obtained in step 3 with a silane mixed solution (mixed by methyltrimethoxysilane, methyltriethoxysilane, anhydrous ethanol, and isopropanol in a mass ratio of 1:2:50:30), then add catalysts ammonium fluoride and dimethylformamide (the mass ratio of ammonium fluoride to dimethylformamide is 1:5), and finally add an ammonia solution (0.2 mol / L) to adjust the pH value of the system to 11. The mass ratio of the above precursor: silane mixed solution: catalyst is 3:8:0.3, the temperature is adjusted to 60°C, and the reaction is carried out for 10 hours to obtain a coal gasification slag wet gel;

[0069] Step 5: Add sodium dodecylbenzene sulfonate to the coal gasification slag wet gel obtained in step 4 to enhance the wet gel. The mass ratio of the coal gasification slag wet gel to sodium dodecylbenzene sulfonate is 1:0.3. The reaction time is 10 hours to obtain an enhanced wet gel. The enhanced wet gel is immersed in anhydrous ethanol for aging treatment. The aging temperature is 50°C and the aging time is 20 hours. After the aging treatment, an aged gel is obtained. The aqueous phase solution in the pores of the aged gel is replaced with anhydrous ethanol multiple times. The replaced gel is then placed in a silane solution for solvent replacement and surface modification to alkylate the silanol group on the gel surface. The silane solution is obtained by mixing trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol in a volume ratio of 3:4:8:3. The mass ratio of the replaced gel to the silane solution is 1:3. After modification for 20 hours, it is washed with n-hexane and finally dried at normal pressure to obtain a mesoporous silicon-based material.

[0070] Figure 1 This is a SEM image of the mesoporous silicon-based material prepared in this example. It can be seen from the image that the mesoporous silicon-based material has a three-dimensional network structure with a pore size of 10-30 nm.

[0071] The mesoporous silicon-based material prepared in this embodiment is used to prepare a mesoporous silicon-based phase change composite material. The specific preparation method is as follows: the above-mentioned mesoporous silicon-based material is mixed with paraffin in a mass ratio of 1:0.4, and the paraffin is dispersed in the internal pores of the mesoporous silicon-based material by ultrasonic oscillation at 95°C. The ultrasonic oscillation time is 1.5 hours to obtain a mesoporous silicon-based phase change composite material.

[0072] Example 4

[0073] A method for preparing a mesoporous silicon-based material based on coal gasification slag comprises the following steps:

[0074] Step 1: Dry the coal gasification slag in an oven at 105°C to constant weight, and use a planetary ball mill to ball mill the dried coal gasification slag for 0.5h. The specific surface area of ​​the ball milled product is not less than 350m 2 / g, and then the ground coal gasification slag is placed in a muffle furnace and calcined at 950℃ for 0.5h, and then ground with a glass mortar to make it all pass through a 75-micron square hole sieve to obtain activated coal gasification slag, weigh 100g of the activated coal gasification slag, and place it in a 500mL three-necked flask, hydrochloric acid (0.5mol / L) and acetic acid (1mol / L) are mixed in a volume ratio of 1:1 to form a mixed acid, and then the mixed acid is added to the three-necked flask according to a solid-liquid ratio of 0.2g / L, and stirred for 3h under 95℃ oil bath heating conditions, and the stirring rate is 500rpm. After the reaction is completed, the solid-liquid separation is carried out by suction filtration to obtain an acid leaching solution and an acid leaching residue, and the acid leaching residue is rinsed with a large amount of deionized water until the washing filtrate is titrated with an AgNO3 solution without white precipitation or turbidity, and the washed acid leaching residue is placed in an oven at 105℃ and dried for 24h to obtain coal gasification acid leaching residue;

[0075] Step 2: Mix the coal gasification acid leaching residue obtained in step 1 with NaOH and Na2SiO3 in a mass ratio of 1:1.2:1.0, heat in a muffle furnace at 550°C for 1 hour, take out, quench in cold water, separate the solid from the liquid by suction filtration, rinse the obtained precipitate with distilled water for 10 times, and then place in a vacuum drying oven at room temperature and vacuum dry for 48 hours to obtain an alkali-melted product;

[0076] Step 3: dissolving the alkali-melted product obtained in step 2 with water to obtain an alkali-melted solution with a concentration of 40 wt%, and mixing it with hexadecyltrimethylammonium bromide and ammonia water in an ammonia solution (0.2 mol / L) at a mass ratio of 1:0.4:7, stirring for 1 hour, adding acetic acid solution (0.6 mol / L) dropwise to the system, adjusting the pH value of the system to 10, and continuing to stir for 12 hours to obtain a coal gasification slag enhanced precursor;

[0077] Step 4: Mix the coal gasification slag enhancement precursor obtained in step 3 with a silane mixed solution (mixed by methyltrimethoxysilane, methyltriethoxysilane, anhydrous ethanol, and isopropanol in a mass ratio of 1:2:50:30), then add catalysts ammonium fluoride and dimethylformamide (the mass ratio of ammonium fluoride to dimethylformamide is 1:5), and finally add an ammonia solution (0.2 mol / L) to adjust the pH value of the system to 11. The mass ratio of the above precursor: silane mixed solution: catalyst is 3:8:0.3, the temperature is adjusted to 60°C, and the reaction is carried out for 12 hours to obtain a coal gasification slag wet gel;

[0078] Step 5: Add sodium dodecylbenzene sulfonate to the gasification slag wet gel obtained in step 4 to enhance the wet gel. The mass ratio of the gasification slag wet gel to sodium dodecylbenzene sulfonate is 1:0.3. The reaction time is 12 hours to obtain an enhanced wet gel. The enhanced wet gel is immersed in anhydrous ethanol for aging treatment. The aging temperature is 50°C and the aging time is 20 hours. After the aging treatment, an aged gel is obtained. The aqueous phase solution in the pores of the aged gel is replaced with anhydrous ethanol multiple times. The replaced gel is then placed in a silane solution for solvent replacement and surface modification to alkylate the silanol group on the gel surface. The silane solution is obtained by mixing trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol in a volume ratio of 3:5:9:4. The mass ratio of the replaced gel to the silane solution is 1:3. After modification for 24 hours, it is washed with n-hexane and finally dried at normal pressure to obtain a mesoporous silica-based material.

[0079] The mesoporous silicon-based material prepared in this embodiment is used to prepare a mesoporous silicon-based phase change composite material. The specific preparation method is as follows: the above-mentioned mesoporous silicon-based material is mixed with paraffin in a mass ratio of 1:0.5, and the paraffin is dispersed in the internal pores of the mesoporous silicon-based material by ultrasonic oscillation at 105°C. The ultrasonic oscillation time is 1 hour to obtain a mesoporous silicon-based phase change composite material.

[0080] Comparative Example 1

[0081] In Comparative Example 1, except that hexadecyltrimethylammonium bromide was not added for enhancement treatment in step 3, other methods were the same as those in Example 1.

[0082] Comparative Example 2

[0083] In Comparative Example 2, except that sodium dodecylbenzene sulfonate is not added for strengthening treatment in step 4, other methods are the same as those in Example 1.

[0084] Comparative Example 3

[0085] In Comparative Example 3, except that the mixed solution of trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol was not added in step 4 for solvent replacement and surface modification, the other methods were the same as those in Example 1.

[0086] The phase change materials were made into mortar lightweight insulation boards and mortar test blocks, and the density, strength and thermal conductivity were tested.

[0087] Preparation method of mortar lightweight insulation board: first, 40 parts of PO 42.5 cement, 8 parts of pulp fiber, 30 parts of 0.6-2.26 mm pottery sand, 20 parts of water, and 2 parts of the above-prepared mesoporous silicon-based phase change composite material are mixed evenly with a mortar mixer, and then poured into a 150mm×150mm mold, and then a press is used to pressurize to 5MPa at a force of 0.1MPa / s, and the pressure is maintained for 3 minutes to obtain a 150mm×150mm×5mm insulation board blank. Finally, the insulation board blank is cured for 7 days to finally obtain the mesoporous silicon-based phase change composite insulation board.

[0088] Preparation method of mortar specimens: first, 40 parts of PO 42.5 cement, 8 parts of pulp fiber, 30 parts of 0.6-2.26 mm ceramic sand, 20 parts of water, and 2 parts of the above-prepared mesoporous silicon-based phase change composite materials are mixed evenly with a mortar mixer, and then a cement mortar vibrating table is used to form a 160 mm × 40 mm × 40 mm mortar specimen, which is removed from the mold and cured for 28 days.

[0089] The test results are shown in Table 1 below:

[0090] Table 1

[0091]

[0092] It can be seen from the test results of the above Examples 1-4 and Comparative Examples 1-3 that the mesoporous silicon-based materials prepared by reinforcing the wet gel with hexadecyltrimethylammonium bromide or sodium dodecylbenzenesulfonate and using a mixed solution of trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol for solvent replacement and surface modification have larger specific surface area and pore volume, and when used in lightweight thermal insulation mortar and insulation board, the mortar has higher flexural and compressive strength and greater thermal conductivity, indicating that the mesoporous silicon-based materials prepared in Examples 1-4 of the present invention have certain structural strength.

[0093] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A mesoporous silicon-based material prepared based on coal gasification slag, characterized in that: It has a three-dimensional network structure with a pore size of 5-30nm and a specific surface area of ​​550-900m 2 / g, pore volume is 0.45-0.80cm 3 / g.

2. A method for preparing a mesoporous silicon-based material based on coal gasification slag according to claim 1, characterized in that: The coal gasification slag is dried and ground, and then subjected to high-temperature activation and acid leaching to remove impurities to obtain coal gasification acid leaching slag, the obtained coal gasification acid leaching slag is mixed with NaOH and Na2SiO3, reacted at high temperature and treated with water to obtain an alkali-melted product, the obtained alkali-melted product is modified with a cationic surfactant to obtain a coal gasification slag enhanced precursor, the obtained coal gasification slag enhanced precursor is subjected to a condensation reaction with silane to obtain a coal gasification slag wet gel, the obtained coal gasification slag wet gel is subjected to surface enhancement treatment, aging, solvent replacement and surface modification, and finally cleaned and dried to obtain a mesoporous silicon-based material.

3. The method for preparing mesoporous silicon-based materials based on coal gasification slag according to claim 2, characterized in that: The SiO2 content in the coal gasification slag is not less than 40%, and the ignition loss is not higher than 15%; the cationic surfactant is hexadecyltrimethylammonium bromide; and the silane is methyltrimethoxysilane and methyltriethoxysilane.

4. The method for preparing mesoporous silicon-based materials based on coal gasification slag according to claim 2, characterized in that: The specific steps are as follows: Step 1: Dry the coal gasification slag to constant weight and grind it into powder using a planetary ball mill to make its specific surface area not less than 350m 2 / g, then subjecting the ground coal gasification slag to high temperature activation and grinding to obtain activated coal gasification slag, mixing the obtained activated coal gasification slag with a mixed acid of hydrochloric acid and acetic acid to acid leaching reaction, separating the solid and the liquid after the reaction, washing the obtained filter residue, and drying to obtain coal gasification acid leaching residue; Step 2: Mix the coal gasification acid leaching residue obtained in step 1 with NaOH and Na2SiO3, heat to react, take out after the reaction is completed, quench in cold water, separate the solid and liquid to obtain a precipitate, wash and dry the precipitate to obtain an alkali-melted product; Step 3: dissolving the alkali-melted product obtained in step 2 in water to obtain an alkali-melted solution, adding a cationic surfactant and an aqueous ammonia solution, stirring for 0.5-3 hours, adding an acetic acid solution dropwise to the obtained mixed solution to adjust the pH value of the system to 8-12, and continuing to stir for 8-24 hours to obtain a coal gasification slag enhancement precursor; Step 4: Mix the coal gasification slag enhancement precursor obtained in step 3 with the silane mixed solution, add a catalyst, and finally add an ammonia solution to adjust the pH value of the system to 10-12, and perform a gelation reaction to obtain a coal gasification slag wet gel; Step 5. Add sodium dodecylbenzene sulfonate to the coal gasification slag wet gel obtained in step 4 to enhance the wet gel to obtain an enhanced wet gel. Place the enhanced wet gel in anhydrous ethanol for aging treatment to obtain an aged gel after the aging treatment. Then, replace the aqueous phase solution in the pores of the aged gel with anhydrous ethanol for multiple times. Place the replaced gel in a silane solution for surface modification. After the modification, wash it with n-hexane and dry it at normal pressure to obtain a mesoporous silicon-based material.

5. The method for preparing mesoporous silicon-based materials based on coal gasification slag according to claim 4, characterized in that: The high-temperature activation process conditions of step 1 are: heating at 600-950°C for 0.5-2h; the hydrochloric acid concentration in the mixed acid of hydrochloric acid and acetic acid in step 1 is 0.1-0.5mol / L, the acetic acid concentration is 0.5-1mol / L, and the solid-liquid ratio of the gasification slag to the mixed acid of hydrochloric acid and acetic acid is 0.14-0.30g / L; the acid leaching reaction conditions are: reacting at 80-120°C for 1-4h.

6. The method for preparing mesoporous silicon-based materials based on coal gasification slag according to claim 4, characterized in that: In step 2, the mass ratio of the coal gasification acid leaching residue to NaOH and Na2SiO3 is 1:1-2:0.5-1.5; the heating reaction conditions in step 2 are: reacting at 550-800°C for 1-4h.

7. The method for preparing mesoporous silicon-based materials based on coal gasification slag according to claim 4, characterized in that: The concentration of the alkaline solution in step three is 20-60wt%; the mass ratio of the alkaline product in step three to the cationic surfactant and the ammonia water in the ammonia solution is 1:0.1-0.8:2-8.

8. The method for preparing mesoporous silicon-based materials based on coal gasification slag according to claim 4, characterized in that: The silane mixed solution described in step 4 is obtained by mixing methyltrimethoxysilane, methyltriethoxysilane, anhydrous ethanol and isopropanol in a mass ratio of 1:2:50:30; the catalyst described in step 4 is obtained by mixing ammonium fluoride and dimethylformamide in a mass ratio of 1:5; the mass ratio of the coal gasification slag enhancement precursor, the silane mixed solution and the catalyst in step 4 is 1-5:5-10:0.1-0.5; the gelation reaction conditions in step 4 are: react at 40-75°C for 4-12h.

9. The method for preparing mesoporous silicon-based materials based on coal gasification slag according to claim 4, characterized in that: The mass ratio of the coal gasification slag wet gel to sodium dodecylbenzene sulfonate in step five is 1:0.1-0.5; the strengthening treatment time in step five is 8-16h; the aging treatment temperature in step five is 45-55°C, and the time is 8-20h; the silane solution in step five is obtained by mixing trimethylchlorosilane, hexamethyldisiloxane, diethanol monoisopropanolamine and polyethylene glycol in a volume ratio of 1-5:1-8:6-12:2-6; the mass ratio of the replaced gel in step five to the silane solution is 1:2-4; the surface modification time in step five is 12-48h.

10. A mesoporous silicon-based phase change composite material and a thermal insulation board prepared from the mesoporous silicon-based material according to claim 1.

Citation Information

Patent Citations

  • Method for simultaneously preparing SiO2 aerogel and zeolite by utilizing fly ash

    CN101538046A

  • Nanometer hierarchical pore silicon-based thermal insulation material for heat distribution pipeline, and preparation method thereof

    CN113072335A

  • Method for preparing silicon dioxide aerogel from coal gasification furnace slag

    CN114014327A

  • Gradient recycling and quality-based utilization method of coal gasification slag

    CN117548473A

  • Coal gasification slag separation process method

    CN118002602A